PENGAWETAN SEBELAS JENIS KAYU DENGAN METODE RENDAMAN PANAS-DINGIN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1987)
A study on the treatability of eleven wood species was carried out using hot and cold soaking  treatment  methods  with Koppers Formula  7 as preservative. Specimens measuring 50 cm x 5 cm x 5 cm were soaked  in five  and ten percent preservative  solution for  a duration  of one, two, and three hours and then allowed to cool while the timber is still soaked in the liquid.  The penetration  and retention  were recorded. From this study  the following   conclusions  could  be drawn:The treatment schedule and concentration  of solution  have a highly significant  effect  on the preservative  penetration  and retention. Much higher retention  was shown  when longer hot soaking  and higher concentration  were employed.